1997
DOI: 10.1103/physrevlett.78.2585
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Orientations in Nanocrystal Fluctuations

Abstract: The dynamical behavior of small particles has been observed by high resolution electron microscopy. Spontaneous structural fluctuations, between various orientations, were observed and quantified. Clear transitions involving appearance and vanishing of twins were detected. Measurements of the angle change between succeeding configurations of the ͗111͘ atomic plane reveal the existence of several preferred angular changes. Twin related transformations give a good fit to the observed angular correlation, which e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 13 publications
2
35
0
Order By: Relevance
“…The starting point to explore these properties is to unravel the atomic structures of the ultrafine clusters. Clusters with diameters larger than 3 nm have been extensively studied by atomic resolution transmission electron microscopy (TEM) over the past few decades345678910111213. However, unambiguous determination of the three-dimensional (3D) atomic structure of ultrafine clusters remains a challenge.…”
mentioning
confidence: 99%
“…The starting point to explore these properties is to unravel the atomic structures of the ultrafine clusters. Clusters with diameters larger than 3 nm have been extensively studied by atomic resolution transmission electron microscopy (TEM) over the past few decades345678910111213. However, unambiguous determination of the three-dimensional (3D) atomic structure of ultrafine clusters remains a challenge.…”
mentioning
confidence: 99%
“…A similar instability of nanoparticles observed in electron microscopy has been reported previously for Bi, [9] Au, [10]- [12] Pd and In, [13] and Pb. [14] Under more extreme conditions (increased electron current density) the Bi particles melt. However, for very high current densities the Bi particles solidify and high-frequency fluctuations similar to the case of lower current density are observed.…”
mentioning
confidence: 99%
“…Twin structures are mainly single and multiple twins -up to 5 twins. At room temperature a twin boundary structure of particles is unstable [21] for particle sizes in the range of <10nm while a stacking faults are quite stable under the same conditions due to its higher energy. The particle structure fluctuates with time between the above configurations.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies performed on small Pb nanoparticles by electron microscopy [21] revealed an unstable structure which is characterized by multiple twinned domains and stacking faults defects. Twinning is a predominant deformation mechanism in fcc metals and especially in Pb [20][21][22][23]. Twin structures are mainly single and multiple twins -up to 5 twins.…”
Section: Discussionmentioning
confidence: 99%